Veterans Transfer Payments and State Per Capita Incomes, 1929, 1939, and 1949 - Schaller, Howard G. (The Review of Economics and Statistics, 1953)
JETERANS transfer payments have become a prominent segment of the income received by individuals. Although adopted to serve other purposes, the payments have important implications for the per capita income differences among the 48 states. The use of the state distribution of income as a policy determinant and as a tool of economic analysis requires a thorough understanding of the factors with which the differences are associated. The present article isolates a specific type of payment for study, and the results will add to the growing body of knowledge concerning the forces underlying the geographic income aggregates.2 Specifically, it should indicate whether the government programs embodying the veterans payments are offsetting or accentuating the state per capita income differences arising from other sources.